Network Coding Data Collecting Mechanism Based on Prioritized Degree Distribution in Wireless Sensor Network - Wei Zhang; Xianghua Xu; Qinchao Zhang; Jian Wan; Naixue Xiong (2011 IFIP 9th International Conference on Embedded and Ubiquitous Computing, 2011)
Wireless sensor network (WSN) is a typical distributed storage system, and network coding technology is developed to enhance the data persistence of WSN. However, the traditional distributed coding strategy may cause serious "cliff effect" in the decoding process, that is to say, few source data can be recovered before sufficient encoded packets are received. Moreover, nodes may fail due to the lack of energy or the influence of the switching of external environment, such as a disaster scenario. Such failures may concentrate in a small region or distribute in the whole deployment area which can severely reduced the decoding efficiency of the persistent data in WSN. In this paper, we propose the PLTCDS (prioritized LT codes based distributed storage) algorithm to improve the data decoding efficiency when the data persistence is assured. The main idea of PLTCDS is that the predefined node broadcasts a beacon to stimulate the nodes to form the network with degree distribution priority. To ensure the effectiveness of storage nodes, PLTCDS introduces a class of cumulative counter scheme to avoid empty storage. Also we discuss about the idea of another type of PLTCDS. Experimental results show that PLTCDS algorithm can enhance the network data collection performance and reduce the influence of "cliff effect".